2016
DOI: 10.18632/oncotarget.9348
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of 6-cinnamamido-quinoline-4-carboxamide impair lysosome function and induce apoptosis

Abstract: Autophagy is a lysosomal degradative process that protects cancer cells from multiple types of stress. In this study, we synthesized a series of derivatives of 6-cinnamamido-quinoline-4-carboxamide (CiQ), and investigated their effects on the proliferation and autophagy of cancer cells in vitro. These derivatives effectively inhibited the proliferation of a broad spectrum of cancer cell lines. Further study revealed that CiQ derivatives may induce autophagy and result in disruption of autophagy propagation. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…However, the exact effect of MAPK/ERK on autophagy activation and maturation has not been de ned and generates controversial results [35]. Increasing evidence demonstrates that prolonged activation of MAPK/ERK induced by drug treatment has been indicated to block the maturation process of autophagy [36,37]. In consistent with these studies, our results indicated that both autophagy and ERK were activated while autophagic ux was impaired after treatment with T-96.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the exact effect of MAPK/ERK on autophagy activation and maturation has not been de ned and generates controversial results [35]. Increasing evidence demonstrates that prolonged activation of MAPK/ERK induced by drug treatment has been indicated to block the maturation process of autophagy [36,37]. In consistent with these studies, our results indicated that both autophagy and ERK were activated while autophagic ux was impaired after treatment with T-96.…”
Section: Discussionsupporting
confidence: 82%
“…5B). Accumulating evidence also indicated that drugmediated activation of MAPK/ERK can impair autophagy maturation by disrupting the fusion between autophagosome and lysosome [36,37].To further determine whether T-96 is capable to modulate the progression of autophagic ux, double tagged mCherry-GFP-LC3B reporter, which is pH sensitive, was transfected into CaP cells to evaluate the fusion e ciency of autophagosome and lysosome. The yellow uorescent represented the number of non-acidic autophagosomes, whereas the red uorescent labeled autolysosomes.…”
Section: T-96 Initiated Autophagy While Blocked Autophagic Ux and Subsequently Induced Apoptosismentioning
confidence: 99%
“…However, the precise role of MAPK/ERK in autophagy initiation or maturation has not been defined and yields controversial results 28 . Accumulating evidence indicates that impaired autophagy through disruption of lysosomal function can be triggered by druginduced activation of MAPK/ERK and thus increases cell death 68,69 . Sustained activation of MAPK/ERK has been shown to inhibit the maturation step of the autophagy process 68 .…”
Section: Discussionmentioning
confidence: 99%
“…ERK-dependent autophagic activity is related to specific autophagy markers, such as LC3B-II, beclin1, BNIP-3 and G-interacting protein (GAIP) ( Ogier-Denis et al, 2000 ; An et al, 2006 ; Cheng et al, 2008 ; Tong et al, 2015 ). In addition, accelerating evidence suggests that activation of MEK1/2-ERK1/2 cascade impairs autophagy by disruption of lysosomal function ( Corcelle et al, 2006 ; Kuo et al, 2016 ). Our study found TBMS1-induced autophagy initiation in melanoma cells by MEK1/2-ERK1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%